Addressing health and safety issues in museums: collaborative teaching between occupational and environmental health sciences and museum studies programs. - Wilson, Mark; Cusack-McVeigh, Holly (Annals of Work Exposures & Health, 2026)
Students enrolled in Occupational and Environmental Health Sciences (OEHS) programs complete a specific curriculum designed to provide students with technical knowledge of industrial hygiene practices. Practical experience in occupational health and safety may depend upon a student's ability to secure internships, but students can benefit from the more thorough integration of practical experience into their academic training. This case study highlights how, through a variety of partnerships, a series of unique experiences related to occupational health and safety in museums were created for OEHS students to apply the health and safety knowledge learned in the classroom to a real-world setting. Students gained both technical and interpersonal skills through these activities and provided services and learning opportunities for museum studies students and museum personnel.